(untitled) (REDEL. Revista Granmense de Desarrollo Local, 2019)
This work was developed in a cultivation house belonging to the UBB of Protected Cultivation of the EMA Paquito Rosales of the Municipality of Yara, with the objective of evaluating bioactive products of seedbeds in trays of the cultivation of the hybrid pepper LPD-5. Three trays were used per treatment, sprinkling the small seedlings 10 days after emerging,onetimewith theQuitoMax and Pectimorfbiostimulants and every 7 days with the efficient microorganism, Treatment 1: Application of efficient Microorganism. (4 mL L-1 of water), Treatment 2: Application of QuitoMax (300 mg ha-1 equivalent to 5 mL per backpack of 16 liters), Treatment 3: Application of Pectimorf (16 mL per backpack of 16 liters), Treatment 4: Control treatment (sprinkle the seedlings with running water). The measurements were made at the time of the transplant by treatments, for which 20 plants were randomly chosen, making the following measurements: Number of leaves per plant, Height of the plants (cm), Length of the roots (cm), Thickness of the stem (mm), Fresh mass (g), Days elapsed until transplant. For the statistical analysis of the data obtained, a simple classification ANOVA and a Tukey mean multiple comparison test were used for the 5% error probability with the Statistical Package Version 10 on Windows. The best results are obtained when the QuitoMax and Pectimorf products are applied, by foliar spray 10 days after the germination corresponding to treatments 2 and 3.